(untitled) (Economic and Political Thought, 2012)
One of the key political discussions taking place in the Federal Republic of Germany at present is the one on the situation of Muslim immigrants coming mainly from Turkey. It is connected with another, equally important one on the purpose to enlarge the European Union with Turkey. German policy towards Turkey’s accession to the European Union is at a difficult point. The overwhelming majority of the present government coalition in Germany is against that accession. Only the Minister of Foreign Affairs, Guido Westerwelle, tried to adopt a more flexible attitude but at present he has lost political importance. There is an open question how this policy will change if – what is very probable – after 2012 election the government coalition changes. The dominating attitudes of the society towards Turkey are unfriendly and it is also a very strong feeling in the opposition party – SPD. Therefore, it is really doubtful whether Social Democrats will insist on the solution that two thirds of the German society reject and that also makes the party members divided.